KROMATOGRAFI LAPISAN TIPIS (KLT) DAN KROMATOGRAFI CAIRAN KINERJA TINGGI (KCKT) DARI SOLASODIN, AD DAN ADD - Julia Kantasubrata; Loyniwati Loyniwati; Jamilah Jamilah; A. T. Karossi (Research Center for Chemistry - LIPI, 1993)
Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC) have been used to separate solasodlne, 4androstene-3,17-dione (AD) dan 1,4-androstadiene-3,17-dione (ADD)resulted from bloconversion process of solasodlne using Mycobacterium phlei DSM 43286. In order to minimize the consumption of materials, the separation condition of HPLC could be looked for through TLC method. Two kinds of chromatographic interaction i.e. normal phase and reversed phase chromatography using respectively silica and CIS as stationary phase have been tried. In normal phase chromatography, there are still difficulties for eluting solasodine from silica column, since solasodine has relatively low Rj value. While in reversed phase chromatography, solasodine could be eluted from CIS column, only if the mobile phase is buffered. The selection of solvent systems for this separation should also consider the relatively low UV-Cut-Off of individual solvent, since detection of solasodine requires operation at 205nm. The minimum limit detection which is measured at 240 11m was found to be 0.92 ng AD and 1.54 ng ADD, while the smallest amount of solasodine which could be detected at 205 nm was 3.39 ng. Diode array detector could be used for confirming the solute peaks produced in bioconverslon process.